Tinjauan Geografis Pengembangan Objek Wisata Pantai Huntete Kecamatan Tomia Timur Kabupaten Wakatobi - Suryani Suryani; Siti Nurindah Sari (Indonesian Journal of Geography Education, 2021)
geographical review of the efforts to develop the Huntete beach tourism object, East Tomia District, Wakatobi Regency.Tourism is the most effective sector to boost Indonesia's foreign exchange, one of the reasons is because the resources needed to develop tourism are located domestically. in the homeland. The role of tourism itself is a sector that can support the progress of a region, especially with the existence of regulations regarding regional autonomy. The purpose of this study is (1) to determine the geographical factors that support the development of the object of Huntete Beach. (2) To find out the efforts made by the government of Wakatobi Regency for the development of Huntete Beach tourism objects. This study uses qualitative data types. This research is a type of field research. The data were obtained by using observation, interview and documentation techniques using triangulation method to examine the abstractness of the data. Data analysis was carried out with data condensation flow, data presentation, and data conclusion/verification. The results of this study are that this beach tourism object has several development efforts consisting of several fields such as adequate transportation, promotional activities, improvement and addition of facilities, human resources, and environmental cleanliness. In addition, this tourist attraction has both supporting and hindering geographical factors in its development, the supporting factors consist of attractions/attractions and water factors and the inhibiting factors consist of location, accessibility and climatic factors